Determination method of rock characteristic stresses based on the energy growth rate - Liu, Xiaohui; Gui, Xin; Qiu, Xue; Wang, You; Xue, Yang; Zheng, Yu (Frontiers in Earth Science, 2023)
Introduction: Precisely determining the characteristic stress value of a rock progressive failure process has important theoretical and practical significance for reasonably defining the rock deformation and failure stage, mechanical mechanism, and design parameters. Methods: Based on the energy characteristics in the process of rock deformation and failure, this paper proposes a new method of rock characteristic stress (EGR) around the index of elastic energy storage capacity, elastic energy growth rate, and dissipative energy growth rate. First, the rationality of the new method is verified by the indoor uniaxial and triaxial loading test data of coal and marble. Second, five different determination methods, namely, lateral strain method, lateral strain difference method, crack strain method, energy dissipation rate method, and volumetric strain method, are compared to further verify the scientific nature of the new method. Finally, the method is applied to the conventional triaxial unloading confining pressure test and true triaxial loading and unloading test of marble, and the new method is fully extended to verify its universality. Results: The results show that the theoretical basis of the EGR characteristic stress determination method is rigorous and sufficient, and the value process is objective and reasonable. Compared with different methods, the EGR method can accurately define the process of rock asymptotic failure, and its corresponding characteristic stress level is well-consistent and in a reasonable range. Discussion: The EGR method is applicable to the conventional triaxial unloading confining pressure test and true triaxial loading and unloading test and has good universality.